Synoptic Conditions and Potential Causes of the Extreme Heavy Rainfall Event of January 2009 Over Mindanao Island, Philippines - Olaguera, Lyndon Mark P (Archīum Ateneo, 2021)
This study investigates the synoptic conditions that led to the heavy rainfall/flood (HRF) event in Mindanao Island, Philippines (122 −127°E; 5 −10°N), on January 2009 (JAN2009 HRF) that are less emphasized in previous works. Extensive flooding was reported over Cagayan de Oro City in the northern part of Mindanao, where the rainfall on January 10, 11, and 13, 2009, exceeded the 99th percentile of daily rainfall records of all January of the city from 1979 to 2017 by almost two times. A similar exceedance was also felt in Hinatuan station over the eastern coast of Mindanao Island on January 15, 2009. The interaction of a cold surge shearline over the northern Mindanao Island and the warm tropical easterlies led to enhanced moisture convergence. The warmer air mass is forced to ascend by the advancing colder air mass because it has lower density than the colder air mass. The enhanced moisture convergence and buoyancy difference by the air masses led to enhanced ascent and consequently rainfall along the cold surge shearline. Further analysis shows that enhanced anomalous easterly and northerly winds at 925 hPa are apparent over the Philippines. The anomalous easterly winds sustained the supply of warmer easterlies and collaboratively interacted with the northerly winds that supplied colder temperature air mass. The climatology of this HRF event was examined for all January from 1979 to 2017. The authors identified 15 other cases that are similar to the JAN2009 HRF event and performed lag composite analyses. The results show that the occurrence of these HRF events is facilitated by the southward expansion of the high-pressure system to the north of the Philippines, enhanced cold and warm temperature advections, and enhanced moisture convergence along the cold surge shearline. The results of this study have important implications for disaster mitigation during the northeast monsoon season when rainfall activities are, in general, less intensive over this region.